Strategi Pembelajaran Pendidikan Agama Islam Dalam Membangun Akhlak Siswa Di SD Negeri 03 Seberang Musi - Nur Istiqomah; Eka Yanuarti (GHAITSA : Islamic Education Journal, 2025)
This study aims to determine how the PAI teacher's learning strategy is, how the students' morals are after the teaching and learning process, and what PAI teacher's learning strategy is effective in building students' morals at SD Negeri 03 Seberang Musi. This study uses a naturalistic qualitative research type, namely a type of research that examines data that describes complex and concrete social realities. In addition, this study uses data collection techniques by means of observation, interviews and documentation. While the data analysis technique is carried out through data reduction, data presentation, and drawing conclusions which are carried out during data collection. The results of this study are that the PAI teacher's learning strategy in building students' morals at SD Negeri 03 Seberang Musi is quite good because the PAI teacher carries out varied learning strategies during the teaching and learning process and is also able to be a role model and at the same time provide good examples to his students, then always provides Directions - Directions of advice that are useful for students such as how we enter the house first to say hello, then how we respect the old and love the young, this is what the PAI teacher conveys to his students.